Éthique de l’enseignant chez quelques romanciers congolais: entre construction et déconstruction - Antsue, Jean Bruno (Ponti/Ponts, 2021)
This article examines the ethics of the teacher among some Congolese novelists. The objective of our study consists in showing that although it is part of the logic of construction / deconstruction from a societal doxa, the role of the teacher is to instruct, train and shape the learner in order to preserve illiteracy. Thus, the teacher must show rigor and psycho-pedagogy in order to safeguard his identity and accomplish his noble mission. To arrive at the relevant results, we adopt sociocriticism and stylistics as the point of approach to justify that the teacher’s ethics rest on characterization.